Exposure to the UV Filter Octyl Methoxy Cinnamate in the Postnatal Period Induces Thyroid Dysregulation and Perturbs the Immune System of Mice - Ferraris, Fausto Klabund; Garcia, Esdras Barbosa; Chaves, Amanda da Silva; Brito, Thais Morais de; Doro, Laís Higino; Félix da Silva, Naína Monsores; Alves, Amanda Soares; Pádua, Tatiana Almeida; Henriques, Maria das Graças M. O.; Cardoso Machado, Tiago Savignon; Amendoeira, Fabio Coelho (Frontiers in Endocrinology, 2020)
Evidence shows the bidirectional communication and regulation between the neuroendocrine and immune systems. Thyroid hormones play key roles in nervous system development and can exert influence on various immune cells contributing to pathophysiological conditions. Octyl methoxycinnamate (OMC) is one of the most commonly used UV filters and has thyroid disrupting effects reported by in vitro and in vivo studies. In the present study, we assessed whether OMC administration in mice dams during the lactational period can cause thyroid disruption and generate immunologic alterations in the offspring. Indirect exposure to the OMC (1000 mg/kg) in the lactational period affects neurodevelopment parameters such as delayed eye-opening and weight gain in mice of both sexes, and these alterations are corroborated by the decrease in the T4 levels present in the pups blood. No significant changes were observed in the thymus of these pups, but there was an increase in the number of lymphocytes in the spleen of the OMC-exposed animals similar to the propyl-thiouracil (PTU)-treated group, a well known thyroid disruptor. OMC modulated the percentage frequency of leukocyte populations in peripheral blood, there was a twofold increase in the number of circulating polymorphonuclear cells. In vitro, OMC exhibited an inhibitory effect on splenocyte proliferation induced by anti-CD3 antibody, however, this effect was reversed with the addition of T4 in the cell culture. In summary, the results of the present study demonstrate the influence of OMC on thyroid dysregulation and its impact on the modulation of the immune system in infants.